Komunikasi Dua Arah sebagai Strategi Membangun Loyalitas Penyewa (Studi Kasus Tenant Relations Mal Artha Gading) - Nadia, Angela; Salman, Doddy (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
loyalty at Artha Gading Mall. Intense competition in the retail industry requires mall management to maintain tenant satisfaction through supportive and sustainable communication practices. This research employs a qualitative case study approach using in-depth interviews, participant observation, and document analysis. The theoretical framework includes Two-Way Symmetrical Communication by Grunig and Hunt (1984), Interpersonal Communication by DeVito (2017), and the RACE Model by Cutlip, Center, and Broom (2006). The findings indicate that Tenant Relations implements adaptive two-way communication through face-to-face interactions, WhatsApp, email, and intranet platforms, supported by cross-departmental internal coordination and HRD training programs. These communication strategies are helping handle complaints, increase satisfaction, build trust, and strengthen tenant loyalty. The results are consistent with previous studies emphasizing the importance of symmetrical and interpersonal communication in organizational relationships. This study contributes to the development of organizational communication research and provides practical recommendations for mall management to strategically enhance competitiveness. Penelitian ini menelaah strategi komunikasi staf Tenant Relations dalam membangun loyalitas penyewa di Mal Artha Gading. Persaingan industri ritel menuntut pengelola mal menjaga kepuasan tenant melalui praktik komunikasi yang mendukung dan berkelanjutan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus melalui wawancara mendalam, observasi partisipatif, serta analisis dokumen internal. Kerangka teori yang digunakan meliputi Two-Way Symmetrical Communication dari Grunig dan Hunt (1984), Komunikasi Interpersonal menurut Devito (2017), serta RACE Model oleh Cutlip, Center, dan Broom (2006). Hasil penelitian menunjukkan bahwa Tenant Relations menerapkan komunikasi dua arah yang adaptif melalui tatap muka, WhatsApp, email, dan intranet, didukung oleh koordinasi internal lintas divisi serta pelatihan oleh HRD. Strategi komunikasi ini membantu dalam menangani keluhan, meningkatkan kepuasan, membangun kepercayaan, dan memperkuat loyalitas tenant. Temuan penelitian sejalan dengan literatur sebelumnya yang menekankan pentingnya komunikasi simetris dan interpersonal dalam hubungan organisasi. Penelitian ini berkontribusi pada pengembangan kajian komunikasi organisasi serta memberikan rekomendasi praktis bagi pengelola mal secara strategis.